PERANCANGAN PROTOTIPE WEB DISEMINASI SENSUS PERTANIAN 2023 DENGAN RESPONSIVE WEB DESIGN - Farid Ridho; -, Faturrokhman (Jurnal Aplikasi Statistika & Komputasi Statistik, 2023)
After carrying out the complete enumeration in the 2023 Agricultural Census, BPS is obliged to present the data that has been obtained through data dissemination, one of which uses a website. However, the previous census web dissemination, ST2013, only got usability testing results of 66.19% and mobile device users had difficulty viewing information on the web. Therefore, we need a ST2023 web dissemination that has a responsive design on all screen sizes. To overcome this problem, researchers conducted a study to design a responsive 2023 Agricultural Census Dissemination Web Prototype using Responsive Web Design techniques. The prototype was then evaluated using usability testing and got a result of 81.64%. Responsiveness and compatibility tests on various browsers have also been carried out and got the results that the prototype is responsive on all screen sizes and performs well in most browsers on different devices.